Pengaruh Word of Mouth terhadap Minat Beli Sepeda Motor Honda pada PT. Kencana Mulia Abadi Gunungsitoli - Laoli , Murni; Mendrofa, Yupiter; Harefa , Idarni; Kakisina, Sophia Molindah (UNIB Press, 2025)
One of the forms of dissemination of the most influential form in marketing is word of mouth (WOM) which is a communication from mouth to mouth. Word of mouth is a process where consumers share their experiences about a product or service with others. This study aims to include the influence of word of mouth on the purchase intention of Honda motorcycles at PT Kencana Muha Abadi Gugutola. Effective word of mouth increases consumer attraction and influences their purchase intention. The quantitative method with data analysis techniques using SPSS is to determine how much influence the sample has in purchasing 100 respondents, namely consumers and regular customers of PT. Kencana Muha Abadi Gugutola. The results of the study indicate that there is an influence of word of mouth on the purchase intention of Honda motorcycles at PT. Kencana Mulia Abadi Gunungsitoli, namely where the test of variables X and Y is declared valid, therefore the results for variable X found a Pearson Correlation value (r count) greater than Table (0.195). And declared valid and for variable Y found a Pearson Correlation value (rhining) greater than Table (0.195) and declared valid. In addition, influence of word of mouth on purchasing interest is 41,2% percent.Consumer interest in PT Kencana Mulia Abadi Gunungsitoli obtained an average of 10 respondents' answers of good criteria. Thus word of mouth has a significant influence on consumer buying interest. This means that word of mouth has an effect on buying interest so that it can increase profits for the company. These findings suggest that effective word of mouth is the key to increasing overall buying interest.